Two Narratives of a Single Event: A Critical Discourse Analysis of Al Jazeera Arabic and CNN Arabic Coverage of Charlie Kirk’s Death - Syakir, Muhammad Wildan; Nugraha, Mugy; Sa'adah, Rd. Siti; Seida, Najwa; Pallawagau, Baso (Prodi Pendidikan Bahasa Arab FTK UIN Sunan Ampel, 2025)
Purpose - This study examines how two major Arabic-language news outlets, Al Jazeera Arabic and CNN Arabic, construct divergent discursive narratives surrounding the death of American conservative activist Charlie Kirk. Design/Methodology/Approach -Employing Teun A. van Dijk’s Critical Discourse Analysis (CDA), this qualitative study analyzes eight news texts published between September and October 2025. The analysis covers three textual levels macrostructure, superstructure, and microstructure, while integrating socio-cognitive models and broader sociopolitical contexts. All quotations from Arabic sources are preserved in their original form to maintain analytical accuracy. Findings - The findings reveal a systematic divergence in media framing between the two outlets. Al Jazeera Arabic situates the incident within a broader narrative of political polarization, ideological conflict, and structural instability in the United States, thereby transforming the event into a symbol of wider sociopolitical crisis. In contrast, CNN Arabic frames the same event as a procedural criminal case, relying predominantly on official statements, law enforcement sources, and institutional discourse. These differences are not merely stylistic, but reflect contrasting socio-cognitive models, editorial ideologies, and institutional orientations regarding the role of journalism and political interpretation. Research Limitation/Implications - Although limited to two outlets, the research demonstrates the usefulness of CDA in unveiling ideological layers and interpretive dynamics in Arab media coverage of U.S. political events.